Cardiovascular Involvement in Kawasaki Disease Is Much More Than Mere Coronary Arteritis - Pilania, Rakesh Kumar; Jindal, Ankur Kumar; Bhattarai, Dharmagat; Naganur, Sanjeev Hanumantacharya; Singh, Surjit (Frontiers in Pediatrics, 2020)
Kawasaki disease (KD) is now a common cause of acquired heart disease in children. Coronary artery involvement is the most serious complication in children with KD. Several non-coronary complications have now been identified in this condition but these are often overlooked. Myocarditis is an integral component of KD and may be more common than coronary artery abnormalities. Pericardial involvement and valvular abnormalities have also been observed in patients with KD. KD shock syndrome is now being increasingly recognized and may be difficult to differentiate clinically from toxic shock syndrome. Endothelial dysfunction has been reported both during acute stage and also on follow-up. This may be a potentially modifiable cardiovascular risk factor.